Strategi Pengembangan Tanaman Cabe Keriting. Di Desa Ladogahar Kecamatan Nita Kabupaten Sikka - Yosefina Y. T. Kabelen (Jurnal Ilmiah Wahana Pendidikan, 2022)
Development prospects are a business that is carried out by paying attention to the environmental conditions of the region both internally which includes strengths and weaknesses and external which includes opportunities and threats. The purpose of prospect theory is to describe how consumers make decisions if there is a condition of uncertainty in the consequences of their choice. The strategies used are, Stability strategy, Retrenchment strategy, Growth strategy, and Combination strategy. The purpose of prospect theory is to describe how consumers make decisions if there is a condition of uncertainty in the consequences of their choice. The strategies used are, Stability strategy, Retrenchment strategy, Growth strategy, and Combination strategy.The results of this study show that the prospect of developing tomato farming in Ladogahar Village, Nita District, Sikka Regency is in the quadrant I position with a value of 5.38 which is the most profitable position for farmers because at this time tomato farming has opportunities and strengths so that it can be utilized. The strategy that must be done in this condition is to change the old strategy by replacing the new strategy, which is to utilize the strength and opportunities for the prospects of developing tomato farming in the future